Pengaruh Kecerdasan Emosional dan Spiritual terhadap Akhlak Siswa di Sekolah Menengah Pertama Se-Kecamatan Bangkinang Kota - Nurhadi Nurhadi; Fitria Fitria (PALAPA, 2020)
This study aims to find the effect of emotional and spiritual intelligence on the morals of students in junior high schools in Bangkinang City District. The purpose of this study are three, namely: 1. To determine the effect of emotional intelligence on the morals of students in the First Middle School in Bangkinang District. To find out the effect of spiritual intelligence on students' behavior in the First Middle School in Bangkinang City District. 3. To find out the significant influence between emotional and spiritual intelligence on the morals of students at the First Middle School in Bangkinang Kota sub-district. This research is a correlational research with a quantitative approach. The population of this study was 2205 students. Research samples were 399 students. Sampling using Slovin formula with an error rate of 5%, sampling technique using Stratified Random Sampling. Data collection techniques in this study using a questionnaire and data analysis techniques using multiple regression. From the results of the study obtained that there is an influence between emotional intelligence on student morals with a Significant value of 0,000 <0.05. There is an influence between spiritual intelligence on student morals with a Significant value of 0,000 <0.05. Then there is a significant influence of Emotional and Spiritual Intelligence on the Morals of Students in Junior High Schools in Bangkinang City District with a Significant value of 0,000 <0.05.